Internet-dependent behavior as a potential risk factor for recurrent headaches among adolescents and young adults of the Republic of Tuva - Panicheva, Elena S.; Sat, Diana A.; Kurganskaya, Tatiana M.; Seren-ool, Sayana S. (The New Research of Tuva, 2024)
The article is devoted to the study of the prevalence and structure of recurrent headache (RH), one of the most common types of functional somatic disorders, among adolescents residing in the Republic of Tuva. It also assesses the role of maladaptive online behavior and certain components of Internet content as possible risk factors for RH among adolescents and young people in Tuva. The authors analyzed the significance of different types of Internet use among Tuvan adolescents and young adults, including adaptive (AIU), maladaptive (MIU), pathological (PIU) and mixed forms, as well as specific forms such as problematic use of computer games and social networks.The source of the analysis was the results from online testing of a random sample of adolescents (2,772 individuals) using Google Forms and psychometric questionnaires. We used screening questionnaires to verify the types of online behavior and the components of internet content. The significance of the indicators as possible risk factors for PH was assessed using odds ratios and their confidence intervals.A large list of risk factors for developing RH due to maladaptive online behavior has been identified. These factors include the gender, age group, and ethnicity of those surveyed. The most significant risk factors for girls are problematic internet use (PIU) and maladaptive internet use (MIU), while for boys, problematic smartphone use is the most significant factor. For the age group 12–14, the most important risk factors are MIU, problematic internet use, dependence on social networks, and an undifferentiated type of problematic internet use. For those aged 15–18, the risk factors include problematic internet and social network use, as well as problematic smartphone use and a mixed type of problematic internet usage.Significant risk factors for Tuvans surveyed (regardless of age and gender) included problematic smartphone use and problematic use of PIU. For Russians, it was problematic computer game use.The likelihood of developing RH among adolescents and young people in Tuva (if risk is assessed for the entire surveyed group, regardless of age, gender, and ethnicity) depends on their online behavior, including problematic smartphone and social network use.
Keywords: teenager; youth; Tuva; recurrent headache; risk factor; Internet; online behavior; addiction; consumed content; Tuvans; Russians